Introducing the FirstLight project: UV luminosity function and scaling relations of primeval galaxies - Ceverino, Daniel; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. We introduce the FirstLight project, which aims to generate a large data base of high-resolution, zoom-in simulations of galaxy formation around the
Gesehen am 09.05.2018